Pemberdayaan Bank Sampah untuk Kesejahteraan dan Kelestarian Lingkungan di Kelurahan Maulafa, Kupang - Fanggidae, Rolland Epafras; Molidya, Aldarine; Faah, Yuri Sandra (Penerbit Goodwood, 2025)
Purpose: The aim of empowering the Mutiara Timor Waste Bank, Maulafa Subdistrict Branch, to improve the economy and preserve the environment.. Methodology/approach: The stages of activities carried out in the implementation of PkM include; a. Lecture method; the expert provides tips for managing waste banks and waste bank management. b. Workshop method; community groups are given special training and assistance to manage waste banks in order to improve the economy through marketing superior products from waste processing and environmental empowerment. c. Focus Group Discussion; conducting discussions with waste bank groups, sub-district officials, community leaders and the PKK of Maulafa Village. Results/findings: The PkM results show that empowering waste banks can be an effective solution for improving the economy and preserving the environment in Kupang City. Waste banks can provide benefits to the community, such as increasing income, opening up business opportunities, and helping to keep the environment clean. Continuous support from the government, universities and the private sector is needed to ensure the sustainability and development of waste banks in Kupang City. Conclusion: The study concludes that waste bank empowment enhances community welfare through economic opportunities, environmental conservation, and active participation. It demonstrates the potential of community-based waste management as a sustainable solution for urban areas. Limitations: The limitation of this study is about how to give education and waste management to optimize the increasing waste. Contribution: The study enhances practical knowledge in waste management, boosts public awareness, encourages community involvement, and highlights income-generation potential while promoting environmental sustainability in Kupang.